Systematic Literature Review on Self Congruity in Tourism Destination - Hajar, Siti; Nafisah, Nia; Wulung, Shandra Rama Panji (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2021)
Tourism destination one of the key concepts of the tourism sector. The rapid growth of tourism destination which have grown rapidly in recent years necessitate marketing as an important factor in tourism destination management. One of the important concepts in the literature of marketing and tourist behavior is self-congruity. Many studies have tested and applied the theory of self-congruity in various industries including tourism destinations with mixed results and findings. The purpose of this study is to generate future research directions by identifying the application of self-congruity in tourism destinations over the last five years. This study uses a systematic literature review method to explain self-congruity in tourism destinations through the identification of ten articles. This literature review research reveals the context of tourism destinations, the variables that have been linked and further research on self-congruity in tourism destinations in the ten articles. This research is the basis for developing self-congruity studies for further research. In addition, this research has a role to provide input to tourism destination stakeholders regarding the application of self-congruity in tourism destination.